Managing receiver-based message logging overheads in parallel applications - Meyer, Hugo (2013)
Using rollback-recovery based fault tolerance (FT) techniques in applications executed on Multicore Clusters is still a challenge, because the overheads added depend on the applications' behavior and resource utilization. Many FT mechanisms have been developed in re- cent years, but analysis is lacking concerning how parallel applications are a ected when applying such mechanisms. In this work we address the combination of process mapping and FT tasks mapping on multicore environments. Our main goal is to determine the con guration of a pessimistic receiver-based message logging approach which generates the least disturbance to the parallel application. We propose to characterize the parallel application in combination with the message logging approach in order to determine the most signi cant aspects of the application such as computation communication ratio and then, according to the values obtained, we suggest a con guration that can minimize the added overhead for each speci c scenario. In this work we show that in some situations is better to save some resources for the FT tasks in order to lower the disturbance in parallel executions and also to save memory for these FT tasks. Initial results have demonstrated that when saving resources for the FT tasks we can achieve 25% overhead reduction when using a pessimistic message logging aproach as FT support.